Factors in selecting tourist destination in Kelantan - Chiong Wen Xin; Mon Thip Sanong; Hoo Jia Ming; Siti Munirah A.Kadir (2021)
Tourist destination is about a place of interest where tourist visit, typically for its inherent or an exhibited natural or cultural value and historical significance. However, this situation focuses on the state of Kelantan since Kelantan is familiar with their culture and the traditional food. Therefore, this research keen to achieve four research objectives. First, to identify the relationship between visiting friends or relatives and selecting tourist destination in Kelantan. Second, to identify the relationship between rest and relaxation and selecting tourist destination in Kelantan. Third, to identify the relationship between cultural exploration and selecting tourist destination in Kelantan. Lastly, to identify the best factor in selecting tourist destination in Kelantan. This research the quantitative approach and involved the distribution of 400 respondents through online survey which is questionnaire. Data from the questionnaire were analysed using Statistical Package for Social Science (SPSS) to generate the quantitative result. Overall, the finding showed that all the independent variables significantly have relationship on selecting tourist destination and cultural exploration is the best factor in selecting tourist destination in Kelantan. The results from this research provided significant contribution in term of theoretical and practical perspectives. This research help other practitioner such as scholars, other researchers, even other tourist to explore and keeping the culture and Kelantan heritage for the next generation in the future and from the theoretical perspective, this research extent the knowledge regarding selecting tourist destination especially for the Kelantan state.